Digital Transformation and Strategic Sponsorship: The Case of BBVA - Santomier, Jr., James; Söderman Sten; Kunz, Reinhard (Quality in Sport, 2020)
The overall purpose of this paper is to describe and explain the strategic sponsorship program of Banco Bilbao Vizcaya Argentaria (BBVA) and, specifically, the partnership of its U.S. subsidiary, BBVA Compass (BBVAC), with the American National Basketball Association (NBA) using a case study method. This paper demonstrates how BBVA, initially through the transformational leadership of former BBVA Group Executive Chairman Francisco González, has leveraged digital transformation and strategic sponsorship to increase its brand equity and revenue. BBVA’s effective sponsorship strategy represents an innovative, agile, and digitally focused model for marketing executives and sport marketers considering a long-term investment in strategic sponsorship. By developing digital assets, leveraging a client-focused business model, and partnering with sport enterprises, BBVA has increased its brand equity and emerged as a leading global financial institution with offices in over 30 countries. BBVAC’s strategic sport and cultural sponsorships, especially its partnership with the NBA from 2010 to 2016, are synergistic with its digital initiatives. This research and its practical implications should enable sport business and marketing professionals to understand the implications of the digital transformation of enterprises for strategic sport sponsorship and provide alternative methods to engage consumers and enhance integrated marketing communications. This case study also should provide insight and direction for further digital transformation and sport management research.